Co-gasification of coal and empty fruit bunch (EFB) in an entrained flow gasification process - Wan Muhamad Syafiq, Wan Ismail; Ruwaida, Abdul Rasid (Universiti Malaysia Pahang, 2017)
In Malaysia, empty fruit bunch (EFB) is one of the major biomass source from the palm oil industry. It is an environmental friendly, renewable and sustainable source of energy, which may be used to generate electricity and other forms of energy. EFB may be converted into synthesis gas (syngas) through the gasification process, or mixed with coal through the co-gasification process. Raw EFB usually consists of high moisture content and low energy density compared to coal. Having a mixture of biomass and coal is one of the method to increase the efficiency of the biomass gasification process. Hence, it is the objective of this work to investigate the co-gasification of coal and EFB at various process conditions, whereby, an entrained flow gasifier was used to investigate the effect of the gasification temperature in the range of 700°C – 900°C, for various coal-EFB mixtures on the syngas composition. The produced gas was collected and quantified using gas chromatography. It was found that when the mass ratio of coal to EFB was increased, the production of hydrogen (H2), carbon monoxide (CO) and carbon dioxide (CO2) also increases. Besides that, the carbon conversion and the higher heating value (HHV) of the gas products also increases with increasing in mass ratio of coal-EFB mixtures. The highest cold gas efficiency (CGE) recorded for coal mixture is 2.72 MJ/m3 . Thus, this shows the potential in co-gasification for producing alternative energy to the conventional fossil fuel resources that is depleting.